Management of Defects on Lower Extremities with the Use of Matriderm and Skin Graft - Jun-Young Choi; Seong-Hun Kim; Gwang-Jin Oh; Si-Gyun Roh; Nae-Ho Lee; Kyung-Moo Yang (Archives of Plastic Surgery, 2014)
Background The reconstruction of large skin and soft tissue defects on the lower extremities is challenging. The skin graft is a simple and frequently used method for covering a skin defect. However, poor skin quality and architecture are well-known problems that lead to scar contracture. The collagen-elastin matrix, Matriderm, has been used to improve the quality of skin grafts; however, no statistical and objective review of the results has been reported. Methods Thirty-four patients (23 male and 11 female) who previously received a skin graft and simultaneous application of Matriderm between January 2010 and June 2012 were included in this study. The quality of the skin graft was evaluated using Cutometer, occasionally accompanied by pathologic findings. Results All 34 patients showed good skin quality compared to a traditional skin graft and were satisfied with their results. The statistical data for the measurement of the mechanical properties of the skin were similar to those for normal skin. In addition, there was no change in the engraftment rate. Conclusions The biggest problem of a traditional skin graft is scar contracture. However, the dermal matrix presents an improvement in skin quality with elastin and collagen. Therefore, a skin graft along with a simultaneous application of Matriderm is safe and effective and leads to a significantly better outcome from the perspective of skin elasticity.